A low power consumption radar system for measuring ice thickness and snow/firn accumulation in Antarctica. Issue 67 (2014) - Uribe, José A.; Zamora, Rodrigo; Gacitúa, Guisella; Rivera, Andrés; Ulloa, David
Abstract: In order to measure total ice thickness and surface snow accumulation in Antarctica, we have designed and built a surveying system comprising two types of radar. This system is aimed at having low power consumption, low weight/volume and low construction cost. The system has a pulse-compression radar to measure ice thickness, and a frequency-modulated continuous wave (FM-CW) radar designed to measure hundreds of meters of surface snow/firn layers with high resolution. The pulse-compression radar operates at 155MHz, 20 MHz of bandwidth; and the FM-CW radar operates from 550 to 900 MHz. The system was tested in December 2010 at Union Glacier (79°46'S, 83°24'W), West Antarctica, during an oversnow campaign, where Union and other nearby glaciers (Schanz, Schneider and Balish) were covered through 82 km of track. Ice thickness of 1540m and snow/firn thickness of 120 m were detected in the area. The collected data allowed the subglacial topography, internal ice structure, isochronous and the snow/ice boundary layer to be detected. Here we describe radar electronics, their main features and some of the results obtained during the first test campaign. Further improvements will focus on the adaptation of the system to be implemented on board airplane platforms.